Analisis Pengaruh Chronotype dan Body Mass Index (BMI) terhadap Tingkat Kantuk Pengemudi - Maya Arlini Puspasari (Jurnal Rekayasa Sistem Industri, 2023)
One of the main causes of Indonesia's increasing accident rate is fatigue and drowsiness, which places Indonesia among the other countries with the highest accident rates. The elements that significantly affect fatigue and sleepiness are individual factors, namely chronotype and Body Mass Index (BMI). Fatigue and drowsiness are evaluated using EEG signal indicators; there have been several related studies that focused on fluctuations in EEG signals under certain operating conditions. However, few studies evaluated the relationship between chronotype and BMI affecting sleepiness. This study aimed to investigate the relationship between chronotype and BMI and tiredness. The KSS questionnaire and EEG signal indicator were used to evaluate sleepiness. The study findings indicate that the beta signal and the driver's BMI have a negative relationship, namely drivers with high BMI are more likely to be sleepy than drivers with low BMI. In chronotype, the moderate morning type shows an increase in Alpha and Theta power compared to other types, caused by circadian rhythms.